Anterior Cable Reconstruction Using the Proximal Biceps Tendon for Large Rotator Cuff Defects Limits Superior Migration and Subacromial Contact Without Restricting Range of Motion. Issue 7 (30th July 2018) - Park, Maxwell C.; Lin, Charles; Kantor, Adam; Itami, Yasuo; McGarry, Michelle H.; Lee, Thay Q.
Objectives: Large rotator cuff defects involving the supraspinatus and infraspinatus tendons, either due to irreparability or after partial repair lack superior capsule support. Any remaining tendon is at risk for tear progression as the tendon must function as both a dynamic tendon and static ligamentous structure. Our purpose was to biomechanically assess an anterior cable reconstruction (ACR) using autologous biceps tendon. We hypothesized that ACR will normalize superior migration and subacromial contact, without limiting range of motion. Methods: Nine cadaveric shoulders were tested using a custom testing system. Glenohumeral kinematics and subacromial contact pressure were measured using a MicroScribe 3DLX and a Tekscan pressure sensor. Each specimen was tested in five conditions: Intact, Stage 2 tear (supraspinatus), Stage 2 tear + ACR, Stage 3 tear (supraspinatus + anterior half of infraspinatus), Stage 3 tear + ACR. ACR involved a biceps tendon tenotomy at the transverse humeral ligament preserving its labral attachment. ACR included "loop-around" suture fixation using two side-to-side sutures and an anchor at the articular margin in order to restore anatomy and secure the tendon along the anterior edge of the cuff defect. ACR was performed in glenohumeral 20° abduction and 60° external rotation. Specimens were tested at 0°, 20°, and 40° of glenohumeral abduction. Total rotational range of motion was measured with 2.2 Nm of torque under a physiologic muscle load. A superiorly unbalanced load was applied to measure superior translation and contact pressure. Repeated measures analysis of variance was used for statistical significance (P < 0.05). Results: The average specimen age was 58 years (range 33-77). Stage 2 and 3 tears showed increased total range of motion at all abduction angles (P < 0.007). ACR after both Stage 2 and 3 tears showed greater total range of motion at 20° abduction (P = 0.035 and P = 0.040) and 40° abduction (P = 0.003 and P < 0.001). The ACR conditions showed significantly higher total ranges of motion compared to Intact (P ≤ 0.007). Superior translation increased significantly from Intact for Stage 2 tears at 7/12 positions (P ≤ 0.014) and Stage 3 tears at all positions except 40° abduction, 90° external rotation (ER) (P < 0.001). At 0° abduction, ACR significantly decreased superior translation for Stage 2 tears at 0°, 30°, and 60° ER (P < 0.01) and Stage 3 tears at 0° and 30° ER (P < 0.001). At 20° abduction, ACR significantly reduced superior translation for Stage 2 tears at 0°, 30°, and 60° ER (P < 0.013) and Stage 3 tears at 0° and 30° ER (P < 0.004). At 40° abduction, ACR significantly decreased superior translation only for Stage 3 tears at 0° ER (P = 0.006). Peak contact pressure significantly increased with Stage 3 tears at 7/12 positions (P ≤ 0.023). ACR significantly reduced peak subacromial contact pressure for Stage 3 tears at: 0° abduction, 30° and 60° ER (P < 0.007); 20° abduction, 30° ER (P < 0.041); 40° abduction, 30° and 60° (peak only) ER (P < 0.024). Conclusion: ACR using autologous biceps tendon can biomechanically normalize superior migration and subacromial contact pressure, without limiting range of motion, similar to superior capsule reconstruction. ACR may improve rotator cuff tendon longevity by providing basic static ligamentous support while helping to maintain normal glenohumeral kinematics.